2021
DOI: 10.1002/cc.20477
|View full text |Cite
|
Sign up to set email alerts
|

Professional development during a crisis and beyond: Lessons learned during COVID

Abstract: This article reviews a virtual professional development program for STEM faculty conducted in 2020 in which, due to COVID, faculty participants had to adjust their teaching practices. The study found that the program's structure, focus, and ability to foster community helped sustain faculty members. Participants shared lessons learned through virtual workshops they led for others on their campuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Content focus and active learning recuring appearance in both periods indicates their vitality in PD leaders’ preparation. PD leaders need to expand their specialized knowledge of mathematics as team PD leaders, they need to experience curriculum-based teaching materials and actively practice solution strategies that assist their facilitation of their team learning ( Borko et al, 2014 , 2021 ; Eddy et al, 2021 ; Loucks-Horsley et al, 2012 ; Prediger et al, 2019a; Smith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Content focus and active learning recuring appearance in both periods indicates their vitality in PD leaders’ preparation. PD leaders need to expand their specialized knowledge of mathematics as team PD leaders, they need to experience curriculum-based teaching materials and actively practice solution strategies that assist their facilitation of their team learning ( Borko et al, 2014 , 2021 ; Eddy et al, 2021 ; Loucks-Horsley et al, 2012 ; Prediger et al, 2019a; Smith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…PD experiences that engage in reflective didactical discussions that are focused on students' thinking and on instructional practices are essential to prepare PD leaders to orchestrate high quality discussions within their teams ( Borko et al, 2014 ; Loucks-Horsley et al, 2012 ; Smith et al, 2020 ). Expert support and group collaboration are vital during leaders’ PD, the first construct a future vision of strong professional skills to lead didactical discussions and the second models the facilitation of team collaboration ( Borko et al, 2014 ; Eddy et al, 2021 ; Polly & Hannafin, 2011 ). Earlier research revealed that providing novice PD leaders with experiences of didactical oriented feedback and reflection prepares them to conduct profound didactical discussions in their teams ( Baker, 2021 ; Darling-Hammond et al, 2017 ; Eddy et al, 2021 ; Loucks-Horsley et al, 2012 ; Smith et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This presented a large challenge when I had to transition everything I did into an online environment while I navigated a new role as chair. Through my participation in Cohort 3 of the SAGE 2YC program (Eddy et al., 2021; Macdonald et al., 2019), I learned from individuals who have traveled similar paths to mine, and I gained confidence in my abilities as a leader and an instructor during the online transition.…”
Section: Angela Daneshmand Assistant Professor Of Earth Sciences Sant...mentioning
confidence: 99%
“…Prior to our abrupt transitions, we were all chosen to be part of a Community of Practice (CoP) within SAGE 2YC for a year‐long virtual professional development program (Eddy et al., 2021). Our cohort of Change Agents consisted of STEM professors from all over the country whose goals were to advance and support the success of all students at our institutions.…”
Section: Getting Into Gear Who Brought the Map?mentioning
confidence: 99%